How useful are commercial corporate governance ratings? Evidence from emerging markets - Black, Bernard; de Carvalho, Antonio Gledson; Kim, Woochan; Yurtoglu, B. Burcin (Journal of Corporate Finance, 2023)
A central issue in evaluating the effects of firm-level corporate governance (FLCG) is how to measure it. We focus here on emerging markets (EMs). One common approach to measuring FLCG uses country-specific (CSIs), tailored to each country's laws and institutions. Several studies report that CSIs can predict firm outcomes in a panel data framework with two-way (firm and time) fixed effects (TWFE). An alternate approach uses commercial CG ratings (CCGRs) that apply the same or similar elements across many countries. We assess the three best available CCGRs covering EMs (Asset4, Thomson Reuters, and MSCI), and find that they do not predict firm outcomes with TWFE in EMs. We also provide evidence that the likely cause for CCGRs' lack of performance is their poor construction rather than the inability of FLCG measures to predict outcomes. CSI-based studies suggest that disclosure (beyond country-mandated minimums) is the FLCG aspect that most consistently predicts firm outcomes in EMs. Yet, these CCGRs have no or minimal measures of disclosure. Other important limitations of the CCGRs include the use of elements that are U.S.-centric; reflect firm outcomes rather than CG; are implausible measures of good FLCG, or are vaguely or subjectively defined. We also attempt, but fail, to use element-level information from CCGRs to construct sound measures of FLCG.